2013
DOI: 10.7482/0003-9438-56-074
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteins profile in Comisana lambs during the first month of life

Abstract: The aim of the present study was to measure the serum total proteins and the serum protein fractions (albumin, α1-, α2-, β-and γ-globulins) of ten newborn lambs (Comisana breed) during the first 30 days of life in order to obtain useful information for neonatal care. From each animal, blood samples were collected via jugular venepuncture at the same hour (9.00) every 3 days for 30 days starting from birth (day 0). The concentrations of serum total proteins and albumin, α1-, α2-, β-, γ-globulins and albumin/glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
5
9
2
Order By: Relevance
“…Similar findings were reported by Szewczuk et al (2011) in calves, who found higher concentrations of α-globulins on day 5 compared to values measured on day 30 of life. In contrast to our results, Piccione et al (2013) recorded a progressive decrease of α 1 -globulins in lambs during the first 2 weeks of life. Many of the acute phase proteins migrate in the α-globulin region (haptoglobin, ceruloplasmin, α 1 -acid glycoprotein, α 1 -antitrypsin), and environmental conditions represent an important trigger for a shift in acute phase proteins.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar findings were reported by Szewczuk et al (2011) in calves, who found higher concentrations of α-globulins on day 5 compared to values measured on day 30 of life. In contrast to our results, Piccione et al (2013) recorded a progressive decrease of α 1 -globulins in lambs during the first 2 weeks of life. Many of the acute phase proteins migrate in the α-globulin region (haptoglobin, ceruloplasmin, α 1 -acid glycoprotein, α 1 -antitrypsin), and environmental conditions represent an important trigger for a shift in acute phase proteins.…”
Section: Discussioncontrasting
confidence: 99%
“…The β-globulins showed a progressive increase of values from the 1 st day of life till the end of the 1 st month. Similar data were reported in goat kids and in lambs by Piccione et al (2011Piccione et al ( , 2013. These findings may be related to the increase of some proteins, especially complement proteins, from this fraction which like the acute phase proteins are involved in the environmental stress response (Bernabucci et al 2009).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings correspond with results reported by Šlosárková et al (2014) and Tóthová et al (2015) in calves and by Nagy et al (2014) in lambs. In contrast to these findings Piccione et al (2011bPiccione et al ( , 2013 reported a subsequent decrease of A/G in comissana lambs and goat kids from the first day after birth to the 13th day of life. According to Alberghina et al (2010) A/G ratio must be interpreted carefully, paying attention to which part of the ratio has changed, because it provides systematic classification and identification of dysproteinaemias.…”
Section: Discussionmentioning
confidence: 81%